Racial and Sociodemographic Disparities in Telehealth Access and Utilization during the COVID-19 Pandemic - Alkawaldeh, Mohammad; Lee, Amanda; Al–Yateem, Nabeel; Dias, Jacqueline; Refaat, Fatma; Rahman, Syed; Subu, Muhammad Arsyad (Open Access Macedonian Journal of Medical Sciences, 2022)
BACKGROUND: Telehealth is not new, but licensing restrictions, HIPAA compliance issues, and lack of reimbursement were significant barriers that hindered its success in the past. Enabling practices to adopt telehealth so that in-person care could be limited to urgent patients and curbed use of finite clinical resources like personal protective equipment for which there was significant shortages. This expansion allowed services including, but not limited to, home visits, therapy services, emergency consults, and nursing facilities visits to be conducted remotely. AIMS: The study objectives are to describe telehealth utilization rates among OB/GYN patients during the first four months of the COVID-19 pandemic by race/ethnicity and insurance coverage and to investigate telehealth access disparities. METHODS: A cross-sectional analysis design was employed. Data abstraction was performed using the electronic medical records of UMass Memorial Medical Center (UMMMC). A convenience sample of 9370 Women who received their telehealth or in-person care at the UMass Memorial Medical Center (UMMMC). RESULTS: Between March 15, 2020, and July 30, 2020, in total, 15,362 encounters were completed. Throughout the timeframe included in this study, 81.34% of appointments were conducted in person, and 18.66% were completed using telehealth. The age of telehealth patients ranged from 17 to 97, with a mean age of 45. Most of the patients were white (n=1202, 63.4%) and held private health insurance (n= 975, 52.4%). Hispanic and Asian patients were less likely to attend their telehealth appointment than patients of other races (p <0.001). Patients with private health insurance were more likely to attend their telehealth appointments than patients with public health insurance (p <0.001). CONCLUSIONS: Telehealth services have been providing patients with access to OB/GYN care during this challenging time and have enhanced health care delivery opportunities. This study identifies a clear need to improve telehealth access and utilization rates among racial and ethnic minority groups and persons with public insurance. Keywords: Telehealth, Health disparity, Telemedicine, Obstetrics